CHARACTER ASSOCIATION AND PATH COEFFICIENT ANALYSIS IN MUNGBEAN - N. HARI SATYANARAYANA*, J. SATEESH BABU, M. S. M. LAKSHMI, G. B. MADHAVI; M. V. RAMANA (The Journal of Research ANGRAU, 2022)
One hundred and sixty germplasms of mungbean (Vigna radiata (L.) Wilzeck.) were evaluated during rabi 2020-21 for yield and its eight contributing traits to study the nature of correlation along with path analysis studies. The seed yield contributing traits viz., number of pods per plant, number of seeds per pod, plant height, number of branches per plant, number of clusters per plant, test weight and days to 50 percent flowering showed significant positive correlation with seed yield; pod length was the only trait which showed non-significant positive association with seed yield in the study. Partitioning of the correlation coefficients of various components upon seed yield into direct and indirect effects revealed that number of pods per plant had high direct effect followed by number of seeds per pod. Highly significant correlation coefficients of all the characters were mainly due to the indirect effects of number of pods per plant followed by number of seeds per pod. This study revealed the importance of the traits such as number of pods per plant, number of seeds per pod, plant height, number of branches and clusters per plant in the crop improvement of mungbean crop.